Denting the FRTB‐IMA Computational Challenge via Orthogonal Chebyshev Sliding Technique. Issue 111 (1st February 2021) - Zenon, Mariano; Ruiz, Ignacio
Abstract : In this paper we introduce a new technique based on high‐dimensional Chebyshev Tensors that we call orthogonal Chebyshev sliding technique. We implemented this technique inside the systems of a tier‐one bank, and used it to approximate Front Office pricing functions in order to reduce the substantial computational burden associated with the capital calculation as specified by FRTB IMA. In all cases, the computational burden reductions obtained were of more than 90 percent, while keeping high degrees of accuracy. The latter obtained as a result of the mathematical properties enjoyed by Chebyshev tensors.